Separation of carbon dioxide from flue gas by mixed matrix membranes using dual phase microporous polymeric constituents. Issue 79 (12th September 2016) - Sekizkardes, Ali K.; Kusuma, Victor A.; Dahe, Ganpat; Roth, Elliot A.; Hill, Lawrence J.; Marti, Anne; Macala, Megan; Venna, Surendar R.; Hopkinson, David
Abstract : Microporous polymeric mixed matrix membranes for CO2 separation from actual flue gas of a coal-fired power plant. Abstract : This study presents the fabrication of a new mixed matrix membrane using two microporous polymers: a polymer of intrinsic microporosity PIM-1 and a benzimidazole linked polymer, BILP-101, and their CO2 separation properties from post-combustion flue gas. 17, 30 and 40 wt% loadings of BILP-101 into PIM-1 were tested, resulting in mechanically stable films showing very good interfacial interaction due to the inherent H-bonding capability of the constituent materials. Gas transport studies showed that BILP-101/PIM-1 membranes exhibit high CO2 permeability (7200 Barrer) and selectivity over N2 (15). The selected hybrid membrane was further tested for CO2 separation using actual flue gas from a coal-fired power plant.